2016
DOI: 10.1111/jopr.12449
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Conditions of Abutments and Non‐Abutments in Removable Partial Dentures over 7 Years of Use

Abstract: RPDs generated more periodontal damage to direct abutments, since higher gingival recession probing depth indexes, and presence of caries and fractures were observed in comparison to indirect abutments and non-abutments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
7
1
3
Order By: Relevance
“…It's interesting to mention that follow-up clinical studies of RPD showed controversial findings regarding the influence of tooth function (direct abutment, indirect abutment or control) on periodontal attachment loss. Contrary to findings showing that tooth function significantly influences gingival recession and probing depth [18,19], Drake and Beck [20] did not find difference in PPD between patients wearing RPDs and not wearing RPDs. In accordance with this, Schmitt et al [13] even identified improvement in periodontal parameters for abutments of unilateral denture compared to the baseline values suggesting that restoration is reliable treatment modality for periodontal health.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…It's interesting to mention that follow-up clinical studies of RPD showed controversial findings regarding the influence of tooth function (direct abutment, indirect abutment or control) on periodontal attachment loss. Contrary to findings showing that tooth function significantly influences gingival recession and probing depth [18,19], Drake and Beck [20] did not find difference in PPD between patients wearing RPDs and not wearing RPDs. In accordance with this, Schmitt et al [13] even identified improvement in periodontal parameters for abutments of unilateral denture compared to the baseline values suggesting that restoration is reliable treatment modality for periodontal health.…”
Section: Discussioncontrasting
confidence: 60%
“…Interesantno je pomenuti da su kliničke studije koje su pratile klasičnu PSP pokazale oprečne nalaze u vezi sa uticajem funkcije zuba (direktni nosač, indirektni, kontrolni zub) na gubitak parodontalnog pripoja. Nasuprot nalazima koji su ukazali na značajan uticaj funkcije zuba na gingivalnu recesiju i dubinu džepova [18,19], rezultati Drake i Beck [20] nisu pokazali razliku u parodontološkom statusu zuba u odnosu na to da li je nošena PSP ili ne. Schmitt i sar.…”
Section: Protetski Postupciunclassified
“…In cross‐sectional studies, where no information is present on the level of self‐performed plaque control and periodontal maintenance or where clearly heterogeneous baseline periodontal conditions are present, partial removable dental prostheses (RDPs) have been associated with increased prevalence of caries, gingivitis, and periodontitis . A study has shown no changes in PD, but increases in plaque levels and gingival inflammation in patients wearing RDPs .…”
Section: Resultsmentioning
confidence: 99%
“…[51][52][53][54] However few studies have attributed RPDs with worsening of periodontal indices of abutment teeth as compared to non-abutment teeth. 50,55 The crux of this reported variation of result lies in the difference of oral and denture hygiene by the patient. 52,56,57 It is recommended that Recall visits should be planned to intercept the development of periodontal pockets.…”
Section: Effect Of Removable Partial Dentures On Periodontal Indicesmentioning
confidence: 99%